Sexual Abuse in Adolescent Girls and Boys with Mild Intellectually Disable - Hassan Zareei Mahmoodabadi; Lila Akrami (Shahid Sadoughi University of Medical Sciences, 2021)
Introduction: The problems of girls and boys with mild intellectually disable (MID) increases with age gradually. Due to the emerging changes, puberty is a significant period for adolescents with MID. The aim of this study to investigate sexual abuse in girls and boys with mild intellectually disable in the puberty period. Methods: This research is a cross-sectional study. The statistical population consisted of all boys and girls with mild intellectual disabilities between the ages of 12 and 16 from exceptional public schools and their mothers in Yazd, Iran. 300 MID adolescents (150 girls and boys each) were selected by multi-stage sampling. To study sexual abuse, a self-designed questionnaire was used. The questionnaire comprised two sections. Kuder-Richardson coefficient obtained for boys and girls with MID turned out to be 0.80 and 0.84, respectively. Using frequency, percentage, and correlation coefficient (p<0.05). Data were analyzed with SPSS 24. Results: In this study, 2.67% (n = 4) of girls and 4% (n = 6) of boys with MID were abused. Also, their psychological and physical signs of sexual abuse were assessed (depression: girls,0.75% (n = 3), boys, 33.33% (n = 2), aggression: girls,0.75% (n = 3), boys, 66.66% (n = 4),  avoiding certain adults, 0.50% (n = 2), boys, 33.33% (n = 2), sleep and eating disorder, 0.25% (n = 1), boys, 16.66% (n = 1) . Some of their parents pointed that their children had not received training in this area. There was a significant positive correlation coefficient between the motherchr('39')s educational level and receiving training by schools and family with sexual abuse knowledge (p<0.05). Conclusion: The irrational reaction of families, the community, and the lack of adequate training lead to an increasein sexual abuse in such individuals. Hence, training these young individuals seems essential both before and during puberty.